Formación integral del alumnado mediante proyectos productivos multimedia en el área de agronegocios - Barrera Puente, María Magdalena (Universidad de Costa Rica, 2021)
Students’ comprehensive education is a challenge in every educative level, that’s why the best intentions often remain in the planning level and far from becoming a regular practice. The following article provides clues of what could be done as a complement for the curriculum to form students in an integral way, based on the experience with the PPMEC program (Productive Multimedia Projects for Continuous Education, as in its acronym in Spanish). This program was tested with a group of students from the Universidad Autonoma Agraria Antonio Narro (UAAAN) Saltillo, Coahuila. Mexico from 2015 to 2019 in the agribusiness area. The theoretical approach focusses on theories and trends emerging in 1993 at UNESCO, which are basic for development of key competences. The following article is a report of the first generation of PPMEC’s experiences, logged in multiple records that form part of the outcomes of this investigation to report levels of the students’ personal development, acquired knowledge, and generated value. The highlights in the main conclusions are the students’ self-confidence, a bigger responsibility in decision making, and most important the legacy of a successful experience that inspirational for later generations PPMEC, proving that it’s possible to learn how to learn and learn how to be, from the same educative project. People’s intentions make the difference.